Sedation mode during endovascular stroke treatment in the posterior circulation: is conscious sedation for eligible patients feasible? - Weyland, Charlotte S.; Chen, Min; Potreck, Arne; Jäger, Laura Bettina; Seker, Fatih; Schönenberger, Silvia; Bendszus, Martin; Möhlenbruch, Markus Alfred (Frontiers in neurology, 2021)
Background and Purpose: To compare safety and efficacy of conscious sedation (CS) vs. general anesthesia (GA) in endovascular stroke treatment (EST) of the posterior circulation (PC).Methods: Retrospective single-center analysis of patients receiving EST for large-vessel occlusion (LVO) in PC between January 2015 and November 2020. Exclusion criteria were severe stroke syndromes (NIHSS > 20), decreased level of consciousness, intubation for transport, and second stroke within 3 months of follow-up. The primary endpoint was a favorable clinical outcome 90 days after stroke onset (mRS 0-2 or 3 if pre-stroke mRS 3). Secondary endpoints were the rate of EST failure and procedural complications.Results: Of 111 included patients, 45/111 patients (40.5%) were treated under CS and 60/111 (54.0%) under GA. In 6/111 cases (5.4%), sedation mode was changed from CS to GA during EST. Patients treated under CS showed a lower mRS 90 days after stroke onset [mRS, median (IQR): 2.5 (1-4) CS vs. 3 (2-6) GA, p = 0.036] and a comparable rate of good outcome [good outcome, n (%): 19 (42.2) CS vs. 15 (32.6) GA, p = 0.311]. There was no difference in complication rates during EST (6.7% CS vs. 8.3% GA) or intracranial bleeding in follow-up imaging [n (%): 4 (8.9) CS vs. 7 (11.7) GA), p = 0.705]. The rate of successful target vessel recanalization did not differ (84.4% CS vs. 85.0 % GA).Conclusions: In this retrospective study, EST of the posterior circulation under conscious sedation was for eligible patients comparably safe and effective to patients treated under general anesthesia.